Developing reading proficiency scales for EFL learners in China - Yongqiang Zeng; Tingting Fan (Language Testing in Asia, 2017)
Abstract Background Since its publication in 2001, the Common European Framework of Reference for Languages has exerted tremendous influence on language learning, teaching, and assessment in China. However, problems were also identified during its application process, thus calling for the localization of the framework. In 2014, the China Standards of English (CSE) project was launched, within which reading scales played a vital part. Methods Following the practice of CEFR, the CSE reading scales employed a similar methodology with revisions. In the initial phase, the theoretical framework was developed and operationalized. Then, a database of reading descriptors was built from both literature and empirical investigations. Finally, qualitative and quantitative measures were implemented to investigate and validate the classification of the descriptors into different categories at distinct levels. Results The paper reports the results of the first two research questions. Based on the synthesis of literature, reading proficiency was defined and four parameters were elicited to describe reading abilities of Chinese EFL learners. A total of 14,467 descriptors were collected, among which 13,893 were deleted after empirical investigations and iterative revisions, thus leaving 574 descriptors in the database. Conclusions Taking 3 years in construction and validation, the reading scales, together with other scales on ability and knowledge within the CSE, will exert tremendous influence on English learning, teaching, and assessment in the nation. However, problems are also expected, which require follow-up research and further revisions based on the feedback of the current version.